2013
DOI: 10.7165/wtr2012.1.4.240
|View full text |Cite
|
Sign up to set email alerts
|

The Area-wide Economic Regions in Korea: Orthodox New Regionalism or Politically-inflicted Regionalism?

Abstract: : The recent interest in regions represents a rise of the new regionalism. Three competing theories provide the frameworks of explaining the ascendance of regions as the meaningful vessel of territorial economic and political processes. They are the orthodox new regionalism, the new politics of scale, and the relational topology of networked actors. Referring to these theories, this paper assesses the establishment of crossprovincial Area-wide Economic Regions (AERs) in Korea. The findings indicate that AERs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Titze et al [21] identified interrelated sectors via national input-output tables in Germany with the help of minimal flow analysis (MFA) and found concentrations of vertical clusters in only 27 of 439 German Nomenclature des Unités Territoriales Statistiques (NUTS)-3 regions. Cho [22] identified the spatial concentrations and linkage properties of industrial clusters in the Chungbuk region of Korea using a three-step approach, which is composed of the cluster index, Getis-Ord's Gi*, and quantitative input-output analysis. Arif and Purnomo [23] identified the location and assessed the economic clusters of leading industries in Surakarta City, Indonesia based on the number of units and labor absorption using the Exploratory Spatial Data Analysis (ESDA).…”
Section: Introductionmentioning
confidence: 99%
“…Titze et al [21] identified interrelated sectors via national input-output tables in Germany with the help of minimal flow analysis (MFA) and found concentrations of vertical clusters in only 27 of 439 German Nomenclature des Unités Territoriales Statistiques (NUTS)-3 regions. Cho [22] identified the spatial concentrations and linkage properties of industrial clusters in the Chungbuk region of Korea using a three-step approach, which is composed of the cluster index, Getis-Ord's Gi*, and quantitative input-output analysis. Arif and Purnomo [23] identified the location and assessed the economic clusters of leading industries in Surakarta City, Indonesia based on the number of units and labor absorption using the Exploratory Spatial Data Analysis (ESDA).…”
Section: Introductionmentioning
confidence: 99%